459 Late-Breaking: Thyroid-stimulating hormone increases mitochondrial oxidative capacity in an in vitro study of equine skeletal muscle. (7th December 2018) - Latham, C; Welsh, T; Fluckey, J; Smith, S; White, S
Abstract: Thyroid-stimulating hormone (TSH) has been shown to increase mitochondrial number and function in human epidermis (Poeggeler et al., FASEB J. 24:1525–1531; 2010). Extrathyroidal action of TSH has not been examined in horses. Therefore, we aimed to test the hypothesis that TSH would increase mitochondrial density and activity in muscle from sedentary mature (n=3; 11 ± 4.6 yr) and aged (n=4; 19 ± 3.6 yr) Quarter horses (4 mares, 3 geldings). Triceps brachii muscle samples (600 mg) were placed into chilled PBS for immediate transport to the laboratory. Tissue from each horse was separated into 8 wells (75 mg/well) containing 2 mL incubation media (DMEM, 5% fetal bovine serum, 10% horse serum, 50 ug/mL gentamycin) with 2 replicates of 4 doses of bovine pituitary TSH (Millipore Sigma): 0 (CON), 2.5 (T2.5), 10 (T10) or 20 (T20) mIU TSH/mL. Alamar Blue (10%) was added to one replicate for each TSH concentration to assess metabolic rate; the second replicate was used for analysis of oxidative capacity (PCI+II) via high-resolution respirometry and mitochondrial number (citrate synthase activity; CS) and function (cytochrome c oxidase; CCO) by colorimetry. Samples were incubated for 18 h at 37oC, 5% CO2. For each horse, values were normalized to CON and data were analyzed using PROC MIXED (SAS v9.4) with TSH dose, age, sex and all interactions as fixed effects. Citrate synthase activity was lower for aged than mature (P=0.0042) and lower for mares than geldings (P=0.0008). However, there was no significant age X TSH or sex X TSH interaction on any of the variables measured. Integrated (per mg protein) PCI+II was higher for T10 than CON, T2.5 and T20 (P=0.012). Thus, 10 mIU TSH in vitro elicited similar increases in oxidative capacity between muscle samples from mature and aged horses of both sexes.